The necessity of a pure water supply - Goodwin, Edith Anna (My University, 1903)
Introduction: One of the great questions of economic importance is that of the purity of water, and, in order to understand this subject, it is necessary to have a knowledge of sources, means of contamination, and methods of purification. Judging from records, the abundant supply of water has been considered of the highest value from remote antiquity. In Genesis, wherever the people pitched their tents, there a well was dug, and quite often dedicated to a superior power, which certainly shows their estimation of its value. In ancient times, centres of population sprang up around those points where water was readily available and great expenditures of labor and treasure were made to carry it to places where it was not naturally plentiful. (Much of the larger constructions connected with ancient water supply were those built for the several systems of irrigation as is shown, in India, by the efforts to preserve and utilize the rains and rivers; and, in Beluchistan, the great Cyclopean dams of stone known as the Ghorbasta were erected (it is believed) 1800 B. C.) By the construction of immense artificial lakes for the conservation of the flood waters of the rivers, the valleys of the Tigris and Euphrates were immense gardens of extreme productiveness. A dam of hewn stone was built at Kosheish to divert the course of the Nile from the spot on which Meua desired to build Memphis, 5800 years ago. Hippocrates, who wrote upon the value of water over 1400 years ago, advised boiling and filtering a polluted water before using it for drinking. He thought that the consumption of swampy water produced enlargement of the spleen.
Citation: Goodwin, Edith Anna. The necessity of a pure water supply. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Water Supply; Purification; Contamination; Water Works; Theses